Gestational trophoblastic tumors: a case series of 18 cases at the university hospital center Mohammed VI of Oujda - Slama, Loubna; Chatbi, Zainab; Bellajdel, Ibtissam; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Gestational trophoblastic tumors (GTTs) are rare but potentially life-threatening diseases arising from the abnormal proliferation of trophoblastic tissue following conception. Their clinical presentation, biological behavior, and metastatic potential vary significantly, complicating both diagnosis and management. We conducted a retrospective observational study over a 9-year period (July 2014 to June 2023) at the university hospital center Mohammed VI of Oujda. Eighteen patients diagnosed with GTTs, including invasive moles and choriocarcinomas, were analyzed in terms of epidemiological, clinical, therapeutic, and prognostic features. The mean age was 35.9 years (range: 19-52). All patients were married and unemployed. Most were referred from external healthcare centers and lived more than 60 km from the hospital. The predominant symptom was abnormal uterine bleeding. Diagnosis was based on abnormal β-hCG trends (89%) or histopathological confirmation (11%). Metastases were present in 43.75% of cases, most commonly in the vagina. Ten patients received chemotherapy: 8 with methotrexate monotherapy and 2 with EMA-CO. One patient underwent hysterectomy for hemorrhage. A favorable therapeutic response was observed, with β-hCG negativation achieved in 90% of patients after nine cycles. Fertility was preserved in most cases. No secondary malignancies were reported. Despite challenges in diagnosis and management, GTTs can be effectively treated with appropriate chemotherapy and close monitoring. Our experience underscores the need for early referral, standardized management protocols, and a national registry to improve patient outcomes.